2021
DOI: 10.3389/fgene.2021.630290
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Driven Color Variation in the Pearl Oyster Pinctada margaritifera var. cumingii (Linnaeus, 1758) Is Associated With Differential Methylation of CpGs in Pigment- and Biomineralization-Related Genes

Abstract: Today, it is common knowledge that environmental factors can change the color of many animals. Studies have shown that the molecular mechanisms underlying such modifications could involve epigenetic factors. Since 2013, the pearl oyster Pinctada margaritifera var. cumingii has become a biological model for questions on color expression and variation in Mollusca. A previous study reported color plasticity in response to water depth variation, specifically a general darkening of the nacre color at greater depth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
2
9
0
Order By: Relevance
“…They also have SNPs impacting pigments from the pterin pathway, a pathway previously identified in Stenger et al (2021aStenger et al ( , 2021b. However, the present results identified a new pathway that was not described before: indeed, we found multiple SNPs impacting genes of the carotenoid pathways.…”
Section: Putative Genetic Control Of the Red Phenotypesupporting
confidence: 57%
See 3 more Smart Citations
“…They also have SNPs impacting pigments from the pterin pathway, a pathway previously identified in Stenger et al (2021aStenger et al ( , 2021b. However, the present results identified a new pathway that was not described before: indeed, we found multiple SNPs impacting genes of the carotenoid pathways.…”
Section: Putative Genetic Control Of the Red Phenotypesupporting
confidence: 57%
“…PurH controls the synthesis of FAICAR molecule (5′‐Phosphoribosyl‐5‐formamido‐4‐imidazolecarboxamide) and can also use PurH as a substrate to produce IMP (Inosine 5′‐monophosphate), the final molecule in the de novo purine nucleotide pathway (Beardsley et al, 1998 ). IMP molecule is the direct precursor to Guanosine 5′ triphosphate (GTP) (Ng et al, 2009 ) and was identified as differentially methylated and potentially involved in the coloration process in the pearl oyster P. margaritifera (Stenger, Ky, Reisser, Cosseau, et al, 2021 ). This specific GTP is involved in the synthesis of yellow pigments in the pterins pathways (xanthopterins and sepiapterins) and in pheomelanin or in eumelanin in the Raper–Mason pathway (Stenger, Ky, Reisser, Cosseau, et al, 2021 ; Stenger, Ky, Reisser, Duboisset, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Yuan et al (2021) identified differently methylated regions related to shell color between brown and white shells, which were primarily enriched in GO functions and pathways relevant to melanin and porphyrin biosynthesis ( Yuan et al, 2021 ). In pearl oyster Pinctada margaritifera , Stenger et al (2021) explored how methylation modifies the color change of the nacre under the change of depth at which an oyster is grown. It is found that the methylation patterns of the four different patterns of clams are different, which may be related to the shell color patterns.…”
Section: Introductionmentioning
confidence: 99%